2016
DOI: 10.22219/jep.v14i1.3890
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Investasi, Pengeluaran Pemerintah Dan Tenaga Kerja Terhadap PDRB Kabupaten/Kota Di Propinsi Banten Tahun 2010-2014

Abstract: The purpose of the study was to determine the effect of variable investment (domestic and foreign), Government Expenditure, Labor (Labor Force Works) for the Gross Regional Domestic Product in Banten Province. The analysis tool used  regression panel data.  the test results obtained deteminasi coefficient R ^ 2 for the fixed effect model of 0.9987. This showed that the ability of independent variables in explaining the dependent variable of 99.87%. The results of the research study concluded that Investment, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
2
1
0
6
Order By: Relevance
“…It can be concluded that the increasing labor will increase the GRDP. This research supports the previous research by Rahman et al (2016), Aziz & Azmi (2017), and Siddique et al (2017) who found that labor has positive significant effect on GRDP. An important factor that determines the prosperity of a society is the level of income.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It can be concluded that the increasing labor will increase the GRDP. This research supports the previous research by Rahman et al (2016), Aziz & Azmi (2017), and Siddique et al (2017) who found that labor has positive significant effect on GRDP. An important factor that determines the prosperity of a society is the level of income.…”
Section: Discussionsupporting
confidence: 91%
“…It can be concluded that the increase of foreign direct investment will increase the GRDP. This research is supported by previous research of Iqbal et al (2014), Agrawal (2015), Rahman et al (2016), Aziz & Azmi (2017), and Siddique et al (2017) who found that domestic investment has a positive effect on GRDP. Investment is a major componen in moving the wheels of a country's economy.…”
Section: Discussionsupporting
confidence: 86%
“…Keempat kabupaten tersebut adalah Tanggerang, Serang, Pandeglang dan Lebak, sedangkan keempat kota yaitu Tanggerang, Serang, Cilegon dan Tanggerang Selatan. Kota Serang dan Tanggerang Selatan merupakan daerah baru hasil pemekaran pada tahun 2008 dan 2009 (Rahman, Soelistyo, & Hadi, 2016).…”
Section: Pendahuluanunclassified
“…Investasi tidak mempengaruhi penyerapan tenaga kerja, karena pemilik usaha dalam menggunakan investasinya lebih cenderung digunakan untuk pembelian barang modal dalam bentuk teknologi sebagai pendukung proses produksi, yang menyebabkan penyerapan tenaga kerja rendah. Rahman et al (2016) Oleh karena itu, pendekatan spasial tidak hanya untuk menganalisis fenomena ekonomi dan sosial, tetapi juga untuk keputusan kebijakan (Karim et al, 2016). Berdasarkan latar belakang diatas dapat diambil rumusan masalah sebagai berikut: 1) Bagaimana dampak spasial yang terjadi antar Provinsi di Indonesia?…”
Section: Pendahuluanunclassified
“…Dengan adanya peningkatan sektor industri akan meningkatkan output yang dihasilkan oleh sektor tersebut, yang nantinya akan meningkatkan nilai kontribu-si terhadap PDRB. Hal ini sesuai dengan penelitian Rahman et al (2016) yang menjelaskan bahwa variabel investasi, pengeluaran pemerintah dan tenaga kerja secara bersama-sama berpengaruh terhadap PDRB. Pengaruh investasi ini juga dikarenakan pemerintah daerah tersebut mampu menyerap dan merealisasikan setiap investasi dengan baik untuk memajukan perekonomian wilayahnya.…”
Section: Pengaruh Investasi Terhadap Pdrb Industriunclassified